Tailored radical hysterectomy for locally advanced cervical cancer. Issue 8 (August 2020) - Sakuragi, Noriaki; Kaneuchi, Masanori; Kato, Tatsuya; Shimada, Chisa; Todo, Yukiharu; Ihira, Kei; Nozaki, Ayako; Umazume, Takeshi; Konno, Yosuke; Mitamura, Takashi; Kobayashi, Noriko; Murakami, Gen; et al.
ABSTRACT : Objective : The survival and prognostic factors for locally advanced cervical cancer treated with nerve‐sparing Okabayashi‐Kobayashi radical hysterectomy have not been elucidated. We aimed to evaluate the oncological outcomes of those patients after radical hysterectomy with adjuvant chemotherapy. Methods : This retrospective cohort study was conducted from January 2002 to December 2011. Treatment was conducted at a single tertiary center in northern Japan. We used the Okabayashi‐Kobayashi radical hysterectomy with lymphadenectomy. We applied unilateral nerve preservation for stage IIA/IIB cancer if there was a one‐sided extension of the disease outside the cervix. Indication for adjuvant therapy was based on Sedlis criteria. High‐risk was defined as evidence of lymph node metastasis, pathological parametrial invasion, and a positive/close surgical margin. The choice of adjuvant therapy was chemotherapy which consisted of paclitaxel and cisplatin. Results : The study included 76 early‐stage IB1 (≤4 cm) and IIA1 cervical cancer and 45 locally advanced stage IB2 (>4 cm), IIA2, and IIB disease treated consecutively. The median follow‐up was 106 (range: 6‐203) months. There were 18 (15%) patients with recurrence, with five of 76 in the early‐stage (7%) and 13 of 45 in the locally advanced disease (29%) (P<0.001). For locally advanced cervical cancer, pT classification (P<0.001), lymph node metastasis (P=0.007), and histology (P=0.05) were associated with locoregional recurrence. The five‐year locoregional recurrence rate in the locally advanced disease was 20% and 5% in the early‐stage disease (P=0.01). The five‐year disease‐free survival in the locally advanced cervical cancer was 71% and 93% in the early‐stage disease (P<0.001). The overall survival in locally advanced disease depended on the adeno‐type histology and lymph node metastasis. Conclusion : The tailored use of nerve‐sparing Okabayashi‐Kobayashi radical hysterectomy with adjuvant chemotherapy based on tumor histology and lymph node metastasis may be a possible option as a treatment of locally advanced cervical cancer in selected patients.